Advancing understanding of the role of IL-22 in myelination: insights from the Cuprizone mouse model - Zamali, Imen; Elbini, Ines; Rekik, Raja; Neili, Nour-Elhouda; Ben Hamouda, Wafa; Ben Hmid, Ahlem; Doghri, Raoudha; Ben Ahmed, Mélika (Frontiers in Neurology, 2024)
Despite significant advancements in the field, the pathophysiology of multiple sclerosis (MS) remains partially understood, with limited therapeutic options available for this debilitating condition. The precise impact of Interleukin-22 (IL-22) in the context of MS is still incompletely elucidated with some evidence suggesting its protective role. To provide a more comprehensive understanding of the role of IL-22, we investigated its effect on remyelination in a mouse model of demyelination induced by Cuprizone. Mice underwent a 6 week regimen of Cuprizone or vehicle, followed or not by intraperitoneal administration of IL-22. Behavioral assessments including tail suspension and inverted screen tests were conducted, alongside histological, histochemical, and quantitative PCR analyses. In Cuprizone-treated mice, IL-22 significantly improved motor and behavioral performance and robustly promoted remyelination in the corpus callosum. Additionally, IL-22 administration led to a significant elevation in MBP transcription in brain biopsies of treated mice. These findings collectively suggest a crucial role for IL-22 in the pathophysiology of MS, particularly in supporting the process of remyelination. These results offer potential avenues for expanding therapeutic strategies for MS treatment. Ongoing experiments aim to further unravel the underlying mechanisms of IL-22 action.